ISLAM DAN EKOPEDAGOGI: GAGASAN PENGEMBANGAN KURIKULUM PAI BERBASIS KESADARAN LINGKUNGAN - Kumaidin, Alip; Hadi, Syaiful (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2026)
This study analyzes the development of an eco-pedagogy–based Islamic Religious Education (PAI) curriculum in response to increasing environmental degradation and declining ecological awareness among students. The research aims to identify the Islamic theological foundations of environmental ethics, formulate sustainability-oriented curriculum strategies for PAI, and examine the role of teachers as eco-pedagogical agents and its impact on students’ ecological behavior. This research employs a qualitative library study using thematic analysis of Islamic texts, eco-pedagogy literature, and contemporary educational studies. The findings indicate that an eco-pedagogy–based PAI curriculum strengthens students’ understanding of tauhid, amanah, and the concept of humans as khalifah (stewards of the earth) in environmental stewardship. Effective implementation requires comprehensive strategies including eco-theological literacy, participatory learning methods, contextual learning, and ecological collaboration. PAI teachers play a central role through modeling, facilitating critical dialogue, and integrating religious values with environmental issues. The curriculum positively impacts ecological behavior, critical awareness, reflective thinking, and students’ moral responsibility for environmental preservation. This study concludes that integrating eco-pedagogy into PAI is a strategic approach to cultivating environmentally conscious and responsible Muslim generations.